Broadband Infrastructure in the Region of Slavonia and Baranja (Croatia) - Mesarić, Dalibor; Ambroš, Franjo; Ivanović, Milan (International Journal of Electrical and Computer Engineering Systems, 2013)
This paper examines issues concerning the development of broadband infrastructure in the region of five counties in Croatia that make up Slavonia and Baranja. It also examines the state of telecommunications in the region today and presents potential models of the development of a broadband network. A new “Slavonian model” of developing a broadband network has been proposed. In this model, new infrastructure investors are to be found among local administration units.